2007
DOI: 10.1111/j.1440-1827.2007.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological investigation of oxidative stress in the post‐genomic era

Abstract: Aerobes, including humans, are consistently exposed to oxidative stress by consuming oxygen. The biological significance of oxidative stress via reactive oxygen and nitrogen species consists of two stages: reversible redox regulation and irreversible oxidative molecular damage, which are sometimes intermingled. During the past decade, many signaling cascades associated with oxidative stress have been discovered. An interaction between Keap1 and the Nrf2 transcription factor is among the most fundamental mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 176 publications
0
27
0
Order By: Relevance
“…(15,25) In the present paper, we not only re-evaluated the catalytic activities of UICC asbestos fibers for the generation of free radicals but also identified several novel characteristics of these fibers in asbestos-induced oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…(15,25) In the present paper, we not only re-evaluated the catalytic activities of UICC asbestos fibers for the generation of free radicals but also identified several novel characteristics of these fibers in asbestos-induced oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species generated during normal cellular metabolism and in response to exogenous genotoxins lead to DNA base damage (Feig et al, 1994;Bjelland and Seeberg, 2003;Toyokuni and Akatsuka, 2007). The predominant DNA repair pathway that removes oxidized and alkylated bases is the BER pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly suggested and demonstrated that exposure of cells to low levels of ROS induces division and proliferation, higher levels induce apoptosis and still higher necrosis (for a review see [63]). Such experiments do not match the complexity of situation in vivo where ROS signaling may involve short localized pulses of ROS nevertheless may reflect some general principles of ROS action.…”
Section: Cell Proliferationmentioning
confidence: 99%